Effect of nanoparticles on the mechanical properties of acrylonitrile–butadiene–styrene specimens fabricated by fused deposition modeling. Issue 7 (8th October 2016) - Meng, Shuna; He, Hui; Jia, Yunchao; Yu, Peng; Huang, Bai; Chen, Jian
ABSTRACT: Acrylonitrile–butadiene–styrene (ABS) nanocomposite filaments with different inorganic nanofillers for fused deposition modeling (FDM) were prepared by melting extrusion and printed via a commercial FDM three‐dimensional printer. The effects of the nanoparticles on the mechanical strength, anisotropy, and thermal properties of the ABS specimens were evaluated. The performances of the virgin ABS samples manufactured by FDM and injection molding were also studied. The results show that the tensile strength (TS) of the pure ABS made by FDM was just up to 70% of the value obtained from the injection‐molded specimens. The mechanical anisotropy of the pure ABS samples was very evident when the building orientation was changed. However, we found that the addition of nanofillers significantly reduced the mechanical anisotropy and improved the mechanical strength and thermostability of the ABS samples fabricated by FDM technology. The TS and flexural strength of the ABS samples increased by 25.7 and 17.1%, respectively, with the introduction of nanomontmorillonite. The addition of nano calcium carbonate lowered the mechanical anisotropy of ABS from 42.1 to 23.9%. © 2016 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2017, 134, 44470. Abstract :